Magnetohydrodynamics Peristaltic Flow of a Couple- Stress with Varying Temperature and concentration for Jeffrey Fluid through a Flexible Porous Medium - saif Razzaq Al-Waily; Dheia G. Salih Al-Khafajy (Al-Qadisiyah Journal of Pure Science, 2021)
The topic of this paper is the peristaltic motion of a non-Newtonian Jeffrey fluid with couple stress across a porous medium inside a horizontal conduit. The unit is strained by a uniform magnetic field. It is taken into account the effects of viscous dissipation, internal heat generation, and radiation. This approach solves the equations of momentum, temperature, and velocity. The numerical formulas for temperature, axial velocity, and velocity are calculated as functionsof the problem's physical parameters. Numerical calculations, as well as the effects of temperature and the inclined slanted magnetic field and concentration on the velocity equation, were conducted for this formula, and the results were shown on the channel wall. The results of the problem's physical parameters In a series of statistics, the effects of this formula are explained numerically and graphically.